Tadpoles of the bromeliad-dwelling frog Phyllodytes luteolus are able to prey on mosquito larvae. Issue 6 (2nd November 2018) - Salinas, Aila S.; Costa, Renan N.; Orrico, Victor G.D.; Solé, Mirco
Abstract : Mosquito-borne diseases have been spreading rapidly. Although Aedes sp. are believed to prefer man-made habitats for reproduction, its larvae can also be found in bromeliads in anthropic environments. Mosquito populations can be controlled through predation, in which the relative size of predator and prey are important to understand this interaction. Tadpoles of Phyllodytes luteolus live in bromeliad axils and are potential predators of mosquito larvae. Our aim was to assess if these tadpoles are able to prey mosquito larvae, and if the predation rate differs according to the size of predator and prey. We collected P. luteolus tadpoles and Culicidae mosquito larvae from bromeliads of restinga (sandbank) areas. We measured the total length of tadpoles and mosquito larvae, and separated them into three size categories (large, medium and small). As experimental units, we used 50 mL centrifuge tubes with 35 mL of dechlorinated water, without substrate and food. We applied nine treatments composed by a combination of tadpole size categories and mosquito larvae size categories. In each unit, we added one tadpole and five mosquito larvae to evaluate the overall predation rate after 4 days. We found that P. luteolus tadpoles of any size were able to prey on mosquito larvae and verified that large tadpoles preyed a larger number of mosquito larvae than smaller size categories. Our results can contribute to evaluate the importance of tadpoles in the trophic structuring of aquatic environments, especially in phytotelmata.